2020
DOI: 10.1108/sajbs-03-2020-0077
|View full text |Cite
|
Sign up to set email alerts
|

Attitude toward social media reviews and restaurant visit intention: a Bangladeshi perspective

Abstract: PurposeWhile the usage of social media reviews has become increasingly popular in recent years, few studies in this context of Bangladesh have investigated its impact on restaurant visit intention. Therefore, this study aims to explain the role of attitude toward social media reviews in customers' restaurant visit intention from the perspective of Bangladesh. In doing so, predictors of attitude toward social media reviews were also ascertained and their indirect effects on restaurant visit intention were inves… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
22
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 24 publications
(31 citation statements)
references
References 79 publications
5
22
1
Order By: Relevance
“…Table 6 shows that zero does not appear between the indirect effects' confidence intervals, providing further empirical evidence for the mediation effect (Hayes, 2017;Popy and Bappy, 2020). As a result, H7 (a-d) have been supported.…”
Section: Structural Model Evaluationmentioning
confidence: 66%
See 4 more Smart Citations
“…Table 6 shows that zero does not appear between the indirect effects' confidence intervals, providing further empirical evidence for the mediation effect (Hayes, 2017;Popy and Bappy, 2020). As a result, H7 (a-d) have been supported.…”
Section: Structural Model Evaluationmentioning
confidence: 66%
“…TAM posits that attitude is the path through which PU and ease of use affect users' behavioral intention (Davis et al, 1989). Prior studies further showed that consumers' PT positively affects adoption intention through their attitude toward adoption (Popy and Bappy, 2020). To the best of the authors' knowledge, the mediating role of attitude in the relationship between barriers of acceptance and behavioral intention has not been studied adequately in the prior studies.…”
Section: Hypothesis Developmentmentioning
confidence: 98%
See 3 more Smart Citations